2021
DOI: 10.1177/03635465211029292
|View full text |Cite
|
Sign up to set email alerts
|

Cell-Free Biomimetic Osteochondral Scaffold for the Treatment of Knee Lesions: Clinical and Imaging Results at 10-Year Follow-up

Abstract: Background: Cell-free devices have been introduced to restore osteochondral defects, avoiding the limitations of cell-based procedures. Among these, an osteochondral scaffold made of type I collagen and hydroxyapatite has been investigated with promising results up to medium-term follow-up. However, the clinical and imaging results over time still need to be documented. Purpose: To evaluate the clinical outcome and tissue maturation at long-term follow-up after the implantation of the osteochondral scaffold. S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…Analysing specifically patellar defects, Perdisa et al documented 34 patients treated with a biphasic cell‐free collagen–hydroxyapatite osteochondral scaffold [17]. They reported a statistically significant improvement in all the clinical scores evaluated at 12 and 24 months of follow‐up compared with the basal evaluation, although with a lower improvement with respect to other studies reporting the outcome of this scaffold for other joint locations [6, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Analysing specifically patellar defects, Perdisa et al documented 34 patients treated with a biphasic cell‐free collagen–hydroxyapatite osteochondral scaffold [17]. They reported a statistically significant improvement in all the clinical scores evaluated at 12 and 24 months of follow‐up compared with the basal evaluation, although with a lower improvement with respect to other studies reporting the outcome of this scaffold for other joint locations [6, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Next, bioactive magnesium (Mg) ions have been introduced in the mineral phase of HAp to enhance the affinity of HAp with natural bone and promote an increase in cell osteogenic activity [ 11 ]. Clinically, this collagen/collagen-magnesium-hydroxyapatite (Col/Col-Mg-HAp) scaffold has demonstrated good stability and clinically relevant improvement in knee function [ [12] , [13] , [14] ]. However, subchondral bone repair remained suboptimal in comparison to the cartilage repair capacity of this scaffold in clinical follow-up [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Preclinically, bi-layered collagen/collagen-magnesium-HAp (Col/Col-Mg-HAp) scaffolds have successfully reconstructed the articular cartilage and the subchondral bone in animal models [ 10 , 11 , 12 ]. Clinical cohort studies also demonstrated the excellent stability of this scaffold and clinical improvement in knee function [ 13 , 14 , 15 ]. However, subchondral bone repair remained suboptimal in some clinical follow-ups in comparison to the cartilage repair capacity of this scaffold [ 15 ], which may lead to altered biomechanical properties of the osteochondral unit and thereby affect the long-term survival of the neo-cartilage [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Clinical cohort studies also demonstrated the excellent stability of this scaffold and clinical improvement in knee function [ 13 , 14 , 15 ]. However, subchondral bone repair remained suboptimal in some clinical follow-ups in comparison to the cartilage repair capacity of this scaffold [ 15 ], which may lead to altered biomechanical properties of the osteochondral unit and thereby affect the long-term survival of the neo-cartilage [ 16 ]. This might subsequently lead to renewed osteochondral damage and joint disease [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%